English translation of isim ma'arifah on surah al-rahman : comparative study of Abdullah Yusuf Ali's and Marmaduke Pickthalls's translation - Nidatul Khasanah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2018)
Mufidah, 1./ws.c.1